Conceptual Extensions of Client-Centered Psychotherapy - Kocharian, Aleksander; Barinova, Nataliia (Psychological Counseling and Psychotherapy, 2025)
The article is devoted to the analysis of client-centered psychotherapy (CCT), namely the key points of its growth. M. Cooper identified different variants of CCT through the metaphor of “flow” or “current”. In the CCT field, four streams meet, merge and dissociate again: ) non-directiveness of the psychotherapist, the client's expertise, and its actualization; 2) helping relationship, necessary and sufficient conditions for client change in psychotherapy, the psychotherapist's intervention has the status of a relationship rather than a technique; 3) experientiality / emotionality, based on Rogers' model of stress - detachment of self from its own experiences, alienation from the natural flow; 4) commitment to social justice, equality and caring interaction with others. The author notes that there may be other streams, which, flowing into the river of CCT, may become dominant there, or may occupy a rather modest place. Streams may also differ in terms of the time of their existence. It is clear that each stream has different theoretical and methodological justifications, and the question of what stream is relevant today, or in other words, what points of growth of SST determine the further development of this psychotherapeutic modality, is extremely relevant. Reflections on the theoretical development of FTAs can be based on two strategies: 1) expanding the conceptual structure of FTAs by drawing on resources external to FTAs; 2) expanding FTAs by drawing on resources internal to FTAs. In the second case, it is not a question of supplementing the FTA, but of its theoretical expansion, related to the reflection of its own theoretical foundations. According to C.S. Hall and G. Lindsey, C. Rogers was an “organismic theorist”, trusting in the rosiness of the naturalness, the naturalness of the therapeutic process. P. Ogden and J. Fisher point to the ongoing shift in the psychotherapeutic paradigm, away from “verbal, linguistic and explicit” towards “nonverbal, bodily and implicit processes”. This paradigm shift is determined by issues of psychotherapy effectiveness. In C. Rogers' description of the process in On Becoming a Person: A Therapists View of Psychotherapy (Boston, 1961), we find the combination of the words “sensory and visceral” six times, and the word “body” twice. The idea of wholeness is embedded in the text, where the body cannot be forgotten. This type of CCT is “bottom up.” CCT has the potential to work with deep brain formations and viscerosensory experiences. In CCT there are two types of healing processes: a causal process from the outside (relationship quality) and a supportive process from within. The second process is revealed through the theoretical extension of the “emotional balancing mechanism”, which is implicitly presented in C. Rogers' approach, and the description of emotional “blockages” formations. Each time gives birth to those theoretical movements that reflect it. In my opinion, today it is neuropsychotherapy and psychotherapeutic technology, as well as an interest in the body. Thus, the beacons of further development of client-centered therapy are the triad: “brain-body-therapeutic techniques”.